IMPLEMENTASI KEPEMIMPINAN VISIONER DAN STRATEGIS DI SMK N 5 PADANG UNTUK MENGHADAPI ERA GLOBALISASI - Savitri, Wici Aan; Giatman, M.; Ernawati, Ernawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: In the globalization era, educational institutions face increasingly complex challenges, including the changing needs of the rapidly evolving industrial and technological world. This research aims to analyze the implementation of visionary and strategic leadership in SMK N 5 Padang in facing the challenges of the globalization era. The method used is a qualitative descriptive study, with data collection techniques through interviews, observations, and documentation studies. The study results show that implementing visionary and strategic leadership at SMK N 5 Padang has improved the quality of education, student competence, and partnerships with industry. This study concludes that visionary and strategic leadership is very effective in facing global challenges, especially in vocational education.Keywords: Visionary Leadership, Strategic Leadership, Vocational School,Globalization.